THE INFLUENCE OF COMPANY'S ROA AND SIZE ON ZAKAT WITH ISLAMIC SOCIAL REPORTING AS MODERATING VARIABLES - Diaz Martha Chairunnisa; Anny Widiasmara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Sharia banking obliged to fulfill all the commands that have been stated in the words of Allah Subhanallahu wata'ala in the Qur'an and obey all the sunnah that has been taught by the Prophet. As a Muslim, it is obligatory to fulfill all the obligatory commands that have been set by Allah, including fulfilling zakat. Zakat must be issued by muzzaki to mustahiq by cultivating noble character both for muzzaki and mustahiq in upholding the Islamic economy. The purpose of this study is to prove empirical evidence of ROA and firm size on zakat and Islamic Social Reporting as moderating. This study uses a quantitative method of secondary data from the Islamic banking sector listed on the Indonesia Stock Exchange with a sample of 13 Islamic Commercial Banks using the 2014-2020 annual financial statements. Profitability is proxied by Return On Assets (ROA) and Company Size using Ln Total Assets. The test method used is descriptive statistical analysis with SPSS 25 hypothesis testing. The results show that ROA and Company Size have a significant effect on corporate zakat and Islamic Social Reporting (ISR) can moderate the effect of ROA and Islamic Social Reporting (ISR) cannot moderate Company Size on corporate zakat.